The Antarctic Climate and the Four Decades of Research in the Brazilian Antarctic Program - Amaral, Cesar; Anjos, Dafne; Donato, Anna; Goldenberg-Barbosa, Rodrigo; Eller, Letícia (Cadernos de Astronomia, 2025)
Antarctica plays a key role in the planet’s climate dynamics. Its characteristic cold climate is responsible for maintaining temperatures, global climate modulation, sustaining ecosystems and ice-dependent biodiversity. Likewise, the region is significantly impacted by global climate change. Over the past few decades, the Brazilian Antarctic Program has been making efforts to study the region, with several modules and facilities used to collect climatic, atmospheric, and biological data, among others. This paper characterizes the Antarctic climate, its importance in the global context, the impacts of climate change on Antarctica, and the efforts of the Brazilian Antarctic Program to study the polar climate.